Deep endometriosis with pericolic lymph node involvement: A case report and literature review - Cacciato Insilla, Andrea (Baishideng Publishing Group Inc, 2014)
Deep infiltrating endometriosis is an often-painful disorder affecting women during their reproductive years that usually involves the structures of the pelvis and frequently the gastrointestinal tract. We present the case of a 37-year-old female patient with an endometrial growth on the sigmoid colon wall causing pain, diarrhea and the presence of blood in the feces. The histology of the removed specimen also revealed the involvement of the utero-vesical fold, the recto-vaginal septum and a pericolic lymph node, which are all quite uncommon findings. To identify the endometrial cells, we performed immunohistochemical staining for CD10 and the estrogen and progesterone receptors.